Application of the Finite Pointset Method to Numerical Modeling of Heat Transferin Two-dimensional Tissue Subjected to a Moving Laser Beam - Korczak, Anna; Saucedo-Zendejo, Felix R. (Computer Assisted Methods in Engineering and Science, 2025)
In this article, a numerical analysis of thermal processes occurring in biological tissue during laser irradiation is presented. The mathematical model is based on the two-dimensional Pennes equation. The analyzed tissue is exposed to the laser irradiation of a moving beam with constant velocity along the tissue surface. The upper face of the skin tissue is subjected to the vertical laser beam, and it is assumed that heat dissipation through convection and radiation from the surface is negligible compared to the heat delivered by the laser beam. Thus, the surface is treated as thermally insulated surface. The effect of the laser beam’s transitional speed and power on the temperature distribution within the skin tissue are investigated. Moreover, the perfusion rate and the effective scattering coefficient are treated as variables dependent on tissue damage. In the computational part of this study, the finite pointset method (FPM) is applied. The temperature distribution computed with FPM is compared with an analytical one obtained for a three-dimensional problem by analyzing a relevant cross-section under the same conditions. This modeling of the dynamic thermal processes within biological tissue subjected to laser irradiation supports the evaluation of biological tissue damage and provides a basis for determining the time and intensity of laser irradiation. In the last part of the article, numerical examples and conclusions are presented.